Stimulating effect of double-stranded yeast RNA on the activity of interferon system genes - A. V. Bateneva; S. G. Gamaley; E. D. Danilenko; R. L. Lebedev (Медицинская иммунология, 2021)
Influence of double-stranded RNA (dsRNA) from Saccharomyces cerevisiae yeast upon expression levels of the macrophage genes encoding TLR3 receptor, interferons alpha and beta (IFNα, IFNβ), 2’,5’-oligoadenylate synthetase (OAS) and protein kinase R (PKR) enzymes has been studied in the J774 mouse histiocytic cell culture and in vivo in Balb/c mice. It has been shown that dsRNA exerts a selective activating effect on genes of TLR3 receptor, antiviral proteins IFNα, IFNβ, and OAS, both in vitro and in vivo. With J774 cell culture, the highest induction capacity was observed for the IFNβ gene: 365 to 802-fold. The stimulatory effect was dependent on the dose of dsRNA in the range of 16.9 to 125 μg/ml. The preparation enhanced IFNα gene activity to lesser degree (more than 10-fold), TLR3 and OAS (3 to 4-fold), while the expression levels for these genes were not significantly dependent on the dose of dsRNA. The stimulating effect of dsRNA was dosedependent in murine peritoneal macrophages. The maximum activating effect of the preparation was shown upon administration of the effective antiviral dose (0.5 mg of dsRNA/kg). Five hours after intraperitoneal injection of dsRNA, the highest level of mRNA synthesis was observed for IFNα (54-fold), OAS (43-fold) and TLR3 (28-fold) genes. Expression of the IFNβ gene increased to a lesser degree (9-fold). An increase in the dose of preparation to 1.5 mg/kg led to decrease of the stimulatory effect. Expression levels of the IFNα, TLR3, and OAS genes in that case decreased by 2-4-fold as compared to a lower dose, and the PKR gene expression was 5-fold lower compared to the control. One day after dsRNA administration, a tendency was observed for both experimental groups towards a decreased transcription of macrophage genes, if compared with the 5-hour term. The weakening of gene activity was less pronounced in animals treated with dsRNA at the dose of 1.5 mg/kg. The transcription indices for IFNβ, OAS, and TLR3 genes were much higher during this period (5-10-fold higher than the control values). The dynamics of PKR gene transcription in both experimental systems was significantly different from the expression of other studied genes. The dsRNA preparation at this dose range did not have a pronounced stimulatory effect upon expression of this gene. A moderate increase in PKR gene activity in macrophages of mice was observed only a day following intraperitoneal administration of dsRNA. Concentrations and length of dsRNA molecules are known to be critical factors to the PKR gene activation. An ability to increase the expression of the gene is shown at low dsRNA concentrations (10-7 g/ml and below), while highly polymeric dsRNAs weaken the gene activity. Since the doses and concentrations of dsRNA used in our experiments were significantly different from those mentioned above, it could, in general, affect regulation of PKR gene transcription towards reduction of the stimulatory effect.